Spatial Analyses of An Integrated Landscape-seascape Territorial System: The Case of The Overcrowded Gulf of Naples, Southern Italy - Appolloni, Luca; Sandulli, Roberto; Bianchi, Carlo Nike; Russo, Giovanni Fulvio (Journal of Environmental Accounting and Management, 2026)
Landscape ecology investigates spatial patterns of natural and anthropogenic ecosystems (anthromes). However, most studies were focused on terrestrial environment, while submarine landscape (seascape) was poorly taken into account. This study represents a first attempt to perform an integrated landscape/seascape spatial analysis of the densely populated Gulf of Naples. Multivariate analyses on landscape metrics were used to detect differences in the spatial patterns of ecosystem patches between landscape and seascape and to compare the effects of anthropogenic impact in terms of spatial heterogeneity. Results showed that landscape, mainly composed by humans perturbed ecosystems, presents higher patch edge dimension, diversity and evenness, and a lower fractal dimension than seascape. Significant differences on edges, diversity metrics, and heterogeneity among patches were also detected between land- and seascape. Landscape showed low γ-variability (a measure of heterogeneity) due to the highly homogenous distribution of ecosystem patches, a characteristic feature of impacted anthropogenic system with low resilience. Conversely, seascape showed high γ-variability, a feature of systems with low anthropogenic impact and high resilience. These outcomes suggest that anthropogenic impact on integrated territorial systems is inversely related to γ-variability, and consequently to resilience. In addition, they also suggest that seascape is more resilient than landscape, also in a highly exploited and overcrowded territorial system like the Gulf of Naples. Such findings can also be useful in support of environmental accounting and management at landscape scale.